2010
DOI: 10.1590/s0102-37722010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Equivalência de estímulos e autismo: uma revisão de estudos empíricos

Abstract: O modelo de equivalência de estímulos oferece uma especificação operacional do comportamento simbólico e tem orientado o ensino e a verificação objetiva de repertórios novos. Pessoas com autismo, caracterizadas por apresentarem, entre outras alterações, graves déficits de linguagem, poderiam se beneficiar de estratégias baseadas neste modelo. Este artigo apresenta uma revisão de publicações de estudos empíricos com autistas, fundamentados no paradigma de equivalência. Os resultados mostraram sucesso de alguns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
7
1
9
Order By: Relevance
“…Furthermore, the difficulty of learning arbitrary relations for people diagnosed with autism spectrum disorders, widely indicated in the literature (Dube & McIlvane, 1995;Eikeseth & Smith, 1992;Gomes & de Souza, 2008;Gomes, Varella, & de Souza, 2010;Kelly, Green, & Sidman, 1998;Vause, Martin, Yu, Marion, & Sakko, 2005;Williams, Pérez-González, & Queiroz, 2005), was not confirmed by this study, considering the data from the EI group. These positive results can be attributed to the set of conditions prepared in the procedure, all recommended by studies on teaching by exclusion trials, and the presence of important repertoires for the performance of the proposed tasks in the participants.…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, the difficulty of learning arbitrary relations for people diagnosed with autism spectrum disorders, widely indicated in the literature (Dube & McIlvane, 1995;Eikeseth & Smith, 1992;Gomes & de Souza, 2008;Gomes, Varella, & de Souza, 2010;Kelly, Green, & Sidman, 1998;Vause, Martin, Yu, Marion, & Sakko, 2005;Williams, Pérez-González, & Queiroz, 2005), was not confirmed by this study, considering the data from the EI group. These positive results can be attributed to the set of conditions prepared in the procedure, all recommended by studies on teaching by exclusion trials, and the presence of important repertoires for the performance of the proposed tasks in the participants.…”
Section: Discussioncontrasting
confidence: 74%
“…Esses resultados confi rmam que os sons recebidos por meio do implante coclear podem compartilhar de funções simbóli-cas, podendo adquirir funções de controle sobre o comportamento dos implantados, assim como ocorre com pessoas com o sistema auditivo preservado (Almeida-Verdu et al, 2008). Esses dados também replicam os encontrados na literatura sobre formação de classes de equivalência com outros tipos de população, como indivíduos com défi cit intelectual (Sidman, 1971) ou indivíduos com autismo e reduzido repertório verbal (Carr, Wilkinson, Blackman, & McIlvane, 2000; ver também a revisão de Gomes, Varella, & de Souza, 2010). Embora o comportamento de leitura não tenha sido diretamente ensinado, esse comportamento tende a emergir, por derivação das contingências de ensino empregadas, que promoveram a formação de classes de equivalência entre palavra ditada, palavra escrita e fi guras (de Rose, de Souza, & Hanna, 1996;de Souza, de Rose, & Domeniconi, 2009).…”
Section: Porcentagem De Acertosunclassified
“…These kinds of performances have been extensively demonstrated in studies using MTS procedure with nonhuman animals (e. g., Iversen, Sidman, & Carrigan, 1986;Sidman, 1992;Kangas & Branch, 2008). Gomes, Varella, and De Souza (2010) and McLay, Sutherland, Church, and Tyler-Merrick (2013) showed that most of the experimental studies using MTS to produce emergent conditional relations with participants with Autism Spectrum Disorder (ASD) reported difficulties in establishing performances involving arbitrary conditional discriminations. However, neither of these studies clearly described training performances in a way that these difficulties could be attributed to the establishment of inadvertent control by location.…”
Section: ________________________mentioning
confidence: 92%